Dimensi Kepribadian Big Five Berdasarkan Orientasi Seksual yang Terjadi di Kota X - Z, Sri Putri Rahayu (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Nowadays, there are many cases of sexual orientation deviations such as homosexuality circulating among society. Homosexuals are a minority whose existence, both from a religious and social perspective, is undesirable, so they often receive various forms of rejection in the social, educational or work environment. , the ban on the existence of homosexuals gave rise to a community called homophobia. The emergence of homophobia as a form of society's rejection of the existence of homosexuals is increasingly common in society. People who have sexual deviance problems are very vulnerable to mental health problems such as anxiety, low self-esteem, unhappiness, problems with sexual satisfaction, use of illegal drugs, depression, and even suicide attempts, in contrast to people who have heterosexual orientation who do not have mental problems related to their sexual orientation. Sexual orientation problems experienced by a person are related to personality. This research aims to determine the differences in the big five personality dimensions based on sexual orientation. The subjects of this research are people who have heterosexual and homosexual sexual orientations, where homosexuals are divided into two groups, namely gays and waria. The number of subjects in this study was 30 heterosexual people, 30 gay people and 30 transgender people. The instrument used for data collection is the big five scale. Data were analyzed using the ANOVA analysis technique. The results of this study show that there are no differences in the big five personality dimensions (neuroticism, extraversion, agreeableness, open to experience and conscientiousness) based on sexual orientation (gay, transgender and heterosexual).